Characterizing the Financial Cycle: Evidence from a Frequency Domain Analysis - Till Strohsal; Christian R. Proa\~no; Jürgen Wolters (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
A growing strand of literature argues that the financial cycle is considerably longer and larger than the business cycle and that its importance is increasing over time. This paper proposes an empirical approach which is suitable to test these hypotheses. We parametrically estimate the whole spectrum of financial and real variables to obtain a complete picture of their cyclical properties. We provide strong statistical evidence for the hypothesized features of the financial cycle for the US and only slightly weaker evidence for the UK. For Germany, however, distinct characteristics of the financial cycle are, if at all, much less visible.
Keywords: C22; E32; E44; 330